2015
DOI: 10.1021/jm501769r
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Mobilizers Targeting Chemokine Receptor CXCR4: Renoprotective Application in Acute Kidney Injury

Abstract: We have discovered a novel series of quinazoline-based CXCR4 antagonists. Of these, compound 19 mobilized CXCR4(+) cell types, including hematopoietic stem cells and endothelial progenitor cells, more efficiently than the marketed 1 (AMD3100) with subcutaneous administration at the same dose (6 mg/kg) in mice. This series of compounds thus provides a set of valuable tools to study diseases mediated by the CXCR4/SDF-1 axis, including myocardial infarction, ischemic stroke, and cancer metastasis. More importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 63 publications
(76 reference statements)
0
38
0
Order By: Relevance
“…The representative CXCR4 ligands include compounds 31 , 80 32 , 154 33 – 34 , 155,156 35 , 157,187 36 , 158 and 37 ; 36 CCR5 ligands include compounds, 38 , 172 39 , 188 40 , 159 41 , 189 42 , 161 43 , 162 and 44 . 163 US28 ligands include compounds 45 , 180 46 , 47 , 181 48 , 182 49 , 181 50 , 184 51 , 185 and 52 .…”
Section: Crystal Structure-based Analysis Of the Effects Of Site-dirementioning
confidence: 99%
See 1 more Smart Citation
“…The representative CXCR4 ligands include compounds 31 , 80 32 , 154 33 – 34 , 155,156 35 , 157,187 36 , 158 and 37 ; 36 CCR5 ligands include compounds, 38 , 172 39 , 188 40 , 159 41 , 189 42 , 161 43 , 162 and 44 . 163 US28 ligands include compounds 45 , 180 46 , 47 , 181 48 , 182 49 , 181 50 , 184 51 , 185 and 52 .…”
Section: Crystal Structure-based Analysis Of the Effects Of Site-dirementioning
confidence: 99%
“…D171 4.60 N, D262 6.58 N, and E288 7.39 Q mutations resulted in a significant decrease of binding of 1 – 13 6872 and 15 , 21 supporting a binding mode in which these negatively ionizable residues are involved in ionic interactions with the positively charged basic nitrogen atoms of ligands 1 – 13 and 15 (Figure 11). SAR studies have indeed indicated that the cationic basic moieties of 15 , 151,152 13 , 153 31 , 78 32 (WZ811), 154 33 , and 34 (155,156) are essential for CXCR4 binding (Figure 11). In addition, Y45 1.39 A, W90 2.60 A, and Y116 3.32 A mutations affected the affinity of 1 , 2 , and 13 , 69 while Q200 5.39 A and H281 7.32 A mutation affected potency of 2 , 3 , and 4 .…”
Section: Crystal Structure-based Analysis Cxcr4 Ccr2 Ccr5 Ccr9 Anmentioning
confidence: 99%
“…It was shown in rat models that treatment with CXCR4 antagonists significantly lowered levels of blood urea nitrogen and serum creatinine 24 hr after bilateral renal ischemia-reperfusion injury. [176][177][178] These data provided evidence that CXCR4 antagonism might be useful to increase circulating levels of adult stem cells or to reduce leukocytes infiltration into kidney, thereby exerting beneficial effects on prevention of ischemic kidney damage.…”
Section: Acute Kidney Injurymentioning
confidence: 91%
“…In a separate study on the ability of the quinazoline analogs to mobilize stem cells, a novel series of triazole ring containing polyamines were synthesized (Fig. ) …”
Section: Therapeutic Potential For Intervention With Cxcl12/cxcr4 Axismentioning
confidence: 99%
See 1 more Smart Citation